EFFECT OF MORINGA OLEIFERA SEED POWDER AS A NATURAL COAGULANT FOR TURBIDITY REMOVAL IN CAPLINA RIVER WATER, PERU - Díaz Pilco, Gabi (2024)
The present research article aims to evaluate the effect of Moringa oleifera as an alternative coagulant for primary water treatment in reducing turbidity. The study included the characterization of the physicochemical parameters of river water. The seeds underwent manual treatment for pulverization and application, and experiments were conducted using a 2x3 factorial design, considering the coagulant dose, sodium hydroxide (NaOH) concentration, and agitation time as variables. The results demonstrated that Moringa oleifera achieved an efficiency of up to 97.77% in turbidity removal. Regarding other parameters, the values complied with the Peruvian Water Quality Standards for potable water production. It is concluded that this method is an environmentally friendly alternative for water treatment, with future considerations for repurposing the residues that may be generated.